Surgery should be routinely videoed - Jesudason, Edwin (Journal of medical ethics, 2023)
Video recording is widely available in modern operating rooms. Here, I argue that, if patient consent and suitable technology are in place, video recording of surgery is an ethical duty. I develop this as a duty to protect, arguing for professional and institutional duties, as distinguished for duties of rescue. A professional duty to protect is described in mental healthcare. Practitioners have to take reasonable steps to prevent serious, foreseeable harm to their clients and others, even if that entails a non-consensual breach of confidentiality. I argue surgeons have a similar duty to patients which means that, provided the patient consents, surgery should be routinely videoed. This avoids non-consensual breaches of patient confidentiality and is aligned with stated professional obligations. An institutional duty to protect means institutions have to take reasonable steps to prevent serious, foreseeable harm at the hands of their surgeons. Rulli and Millum highlighted how institutions can meet their duty using a more consequentialist approach that balances wider interests. To test the force and scope of such duties, I examine potential impacts of routine videoing on aspects of autonomy, justice, beneficence and non-maleficence. I find routine videoing can benefit areas including safety, candour, consent and fairness in access (to surgical careers and expertise). Countervailing claims, for example, on liability, confidentiality and privacy can be resisted—such that where consent and the technology are in place, routine videoing meets a duty of easy protection. In other words, its use should be standard of care.